Absolute midnight - Barker, Clive, 1952- (New York : Joanna Cotler Books, 2011)
Candy Quackenbush of Chickentown, Minnesota, is the only person who can stop the evil Mater Motley who, now that the hour of midnight has come, is prepared to unleash the end of the world.
Booklist
Kirkus Reviews
12-19.
7-12.